Risk Determination, Prioritization, and Classifying in Construction Project Case Study: Gharb Tehran Commercial-Administrative Complex. (13th October 2015) - Sohrabinejad, Azadeh; Rahimi, Mehdi
Abstract : Construction projects play an important role in infrastructure projects in developing countries. According to type, size, and complexity of the project, the number and importance of each risk could be different and many projects cannot reach the project goals due to exposure to multiple risks. Many papers have been published on the subject of risk management in construction projects; unfortunately most of them have not been implemented in practical conditions. The aim of this study is to identify and prioritize risks in construction projects. The classical approach used probability and impact for risk assessment, but these criteria do not sufficiently address all aspects of projects risks and there might be a relationship between different criteria. This study proposes the hierarchical dependencies between criteria. A case study of construction project is presented to illustrate performance and usage of the proposed model. Utilizing library studies and interview with experts, managers, and specialists, decision criteria were identified through brain storming. Risks were categorized by the experts into eleven risks. Important risks were evaluated based on the fuzzy ANP, fuzzy DEMATEL, and fuzzy TOPSIS methods. The proposed model is more suitable than the traditional decision-making methods in prioritizing risk concerning cost, time, and quality.